Does Factor Accumulation or Productivity Change Drive Output Growth in the Indian Sugar Industry? An Inter-state Analysis - Nitin Arora; Sunil Kumar (Contemporary Economics)
The study endeavors to break down output growth in the Indian sugar industry into the ‘perspiration’ component that corresponds to factor accumulation and the ‘inspiration’ component that corresponds to the total factor productivity (TFP) growth. The bootstrapped Malmquist productivity index has been used as a technique to obtain the TFP growth from the period 1974/75 to 2004/05. Empirical analysis reveals that output growth in the Indian sugar industry is equally driven by the inspiration component (i.e., TFP growth) and the perspiration component (i.e., factor accumulation), but in opposite directions. The inspiration component is observed to contribute to output growth positively, whereas the perspiration component contributes negatively. Given substantial TFP growth, the potential output growth in the Indian sugar industry has been restricted primarily by the negative growth of inputs during the entire study period and particularly in the post-reform period.